2022
DOI: 10.3390/catal12101125
|View full text |Cite
|
Sign up to set email alerts
|

Octahedral Cluster Complex of Molybdenum as Oil-Soluble Catalyst for Improving In Situ Upgrading of Heavy Crude Oil: Synthesis and Application

Abstract: Heavy oil resources are attracting considerable interest in terms of sustaining energy demand. However, the exploitation of such resources requires deeper understanding of the processes occurring during their development. Promising methods currently used for enhancing heavy oil recovery are steam injection methods, which are based on aquathermolysis of heavy oil at higher temperatures. Regardless of its efficiency in the field of in situ upgrading of heavy oil, this technique still suffers from energy consumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Perhaps the main enhanced oil recovery methods, which are undergoing a revolution in terms of extracting unconventional oils, are thermally enhanced oil recovery. In their studies, the authors have shown the potential use of in situ combustion on heavy and extra-heavy oil recovery. Other studies have improved the main role of aquathermolysis in improving the heavy oil conversion process.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the main enhanced oil recovery methods, which are undergoing a revolution in terms of extracting unconventional oils, are thermally enhanced oil recovery. In their studies, the authors have shown the potential use of in situ combustion on heavy and extra-heavy oil recovery. Other studies have improved the main role of aquathermolysis in improving the heavy oil conversion process.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the quality of heavy oil and natural bitumen, various upgrading techniques are in use. , Steam-based methods like cyclic steam stimulation and steam-assisted gravity drainage are prevalent, along with cold heavy oil production and solvent-based flooding techniques. Despite their efficacy, steam-based methods have downsides such as high energy consumption for steam generation and extensive freshwater use, leading to low efficiency and potential conflicts with net-zero emissions goals.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the oil's rheological characteristics and ensure reliable and cost-effective crude oil transportation, a series of methods (such as thermal treatment, adding pour point depressant, blending with light oil, sequential transportation, or a combination of various transportation methods) have been presented [6][7][8][9][10][11][12]. Among them, blending with light oil is a commonly used and reliable method.…”
Section: Introductionmentioning
confidence: 99%